2016
DOI: 10.18805/ajdfr.v3i1.3577
|View full text |Cite
|
Sign up to set email alerts
|

Development and quality assessment of Functional Food Supplement (FFS) for the management of lifestyle diseases

Abstract: Lifestyle diseases are found to be rapidly increasing in frequency, in both developed and developing countries due to industrialization and faulty dietary habits. Several agents used to correct these diseases do not become healthy alternatives as besides being expensive they produce a wide spectrum of adverse effects. In this context, a study was conducted to develop a Functional Food Supplement (FFS) using locally available food items that are inefficiently used in daily diet due to ignorance or over sight bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The global market situation of functional food Lifestyle diseases are rapidly increasing in frequency, in both developed and developing countries due to industrialization and faulty dietary habits. (KRISHNAJA AND UKKURU, 2016). Numerous studies in literature showed that there is an increasing popularity in the use of functional food and dietary supplements as well.…”
Section: Introductionmentioning
confidence: 99%
“…The global market situation of functional food Lifestyle diseases are rapidly increasing in frequency, in both developed and developing countries due to industrialization and faulty dietary habits. (KRISHNAJA AND UKKURU, 2016). Numerous studies in literature showed that there is an increasing popularity in the use of functional food and dietary supplements as well.…”
Section: Introductionmentioning
confidence: 99%